2015
DOI: 10.1016/j.cllc.2014.08.005
|View full text |Cite
|
Sign up to set email alerts
|

How Do Elderly Poor Prognosis Patients Tolerate Palliative Concurrent Chemoradiotherapy for Locally Advanced Non–Small-Cell Lung Cancer Stage III? A Subset Analysis From a Clinical Phase III Trial

Abstract: Elderly patients aged ≥ 70 years with unresectable, stage III, locally advanced, NSLCL and a poor prognosis can tolerate CRT with the doses adjusted to age and palliative intent. These results indicate that CRT can provide both survival and QOL benefits in elderly patients, except for those with PS 2 or worse. The male predominance in the ≥ 70-year-age group and the reduced chemotherapy intensity for the patients aged > 75 years might explain the lack of significant survival improvement among those patients ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…12 In another subset analysis, the advantages of CC appeared preserved for the elderly. 13 Both of these recent studies have limitations. Perhaps the largest is the undefined nature of this patient population.…”
Section: Narrativementioning
confidence: 99%
“…12 In another subset analysis, the advantages of CC appeared preserved for the elderly. 13 Both of these recent studies have limitations. Perhaps the largest is the undefined nature of this patient population.…”
Section: Narrativementioning
confidence: 99%
“…For patients in early stage (I/II), surgery provides the best chance for cure (Brunelli, Kim, Berger, & Addrizzo‐Harris, ; Handforth et al, ). For inoperable LSqCC patients (stage III/IV), the prognosis remains poor (Strom, Bremnes, Sundstrom, Helbekkmo, & Aasebo, ). To evaluate the predictive values of lincRNA candidates in LSqCC staging, logistic regression was performed and ORs were calculated in 497 PT samples with definite tumor stage.…”
Section: Resultsmentioning
confidence: 99%
“…The elderly was defined as patients aged ≥70 years in accordance with common practice. 5 , 8 , 18 , 21 , 22 Age was a stratification factor specified in the original protocol. The aims of this analysis were to 1) explore the characteristics, treatment, prognosis, and safety of therapy in elderly patients (aged ≥70 years) with advanced NSCLC; 2) compare the results with those of younger patients.…”
Section: Methodsmentioning
confidence: 99%
“… 6 , 7 Some trials suggested that elderly patients have a poor prognosis and unresectable tumor. 8 Other studies have showed that lung cancer in young patients may constitute an entity with distinct clinicopathologic characteristics. 9 , 10 Thus, it is still controversial whether younger patients have better or worse outcomes compared with the older counterparts with lung cancer.…”
Section: Introductionmentioning
confidence: 99%